Energy transfer in biomimetic and biosensing molecular nanomaterials - Chen, W; Wei-Hsin Chen (2013)
This thesis is concerned with ultrafast photophysics and excitation energy transfer in biomimetic and biosensing molecular nanomaterials, which have been investigated using timeresolved photoluminescence spectroscopy. Artificially-synthesised fully pi-conjugated nanorings with 6-24 units of porphyrins incorporated have demonstrated remarkable full delocalisation of the absorbing excited state across the entire ring on an ultrafast timescale. The largest ring of 24 porphyrin units with a diameter of ~10 nm is the largest man-made molecular nanoring at present. The constraint that the lowest electronic transition is forbidden due to their high molecular symmetries is released by static and dynamic distortions in the solution. These findings provide promising opportunities for using these man-made light-harvesting materials that match the efficiency of their natural counterparts in technological applications. On the other hand, self-assembled organic fluorescent nanoparticles (NPs) formed of amphiphilic monomers with targeting ligands exhibit potential to be used in bio-sensing applications. Homotransfer and heterotransfer of excitation energy in nanoparticles have been investigated, where mannose covalently linked on Amp1-B monomers provide binding sites for Concanavalin A which is attached with energy acceptors. Increasing the molar ratios of Amp1-B-mannose and Amp3-B can increase the binding sites and forming directional energetic cascades towards the NP surface, respectively. However, the amount of these two monomers must be optimised in order to reach the highest donor-acceptor energy transfer rate in the system.